Association of Endocrine Disrupting Chemicals, Bisphenol A and Phthalates, with Childhood Obesity: A Systematic Review - Maryam Zarean; Parinaz Poursafa; Mohammad Mehdi Amin; Roya Kelishadi (Mazandaran University of Medical Sciences, 2018)
Context: Exposure to endocrine-disrupting chemicals (EDCs) can contribute to the risk of childhood and adolescent obesity. Objectives: The aim of this study was to systematically review the literature concerning the association of bisphenol A (BPA) and phthalates with obesity in children and adolescents. Data Sources: Scopus, ISI Web of Science, PubMed, Google Scholar, and Medline were searched to identify studies published up to January 2017. A secondary reference review of all extracted articles was also conducted. Study Selection: All studies that had assessed the relationship between BPA and phthalates with obesity in children and adolescents were included in the present systematic review. Finally, 35 studies were relevant. Data Extraction: The current review was conducted and reported in accordance with the Preferred Reporting Items for systematic reviews and meta-analyses (PRISMA) statement. Results: Thirty-five original studies met the inclusion criteria, consisting of 20 cross sectional, 3 case control, 11 cohort studies and one clinical trial study. Nineteen studies reported that childhood exposure to environmental chemicals including BPA and phthalic acid esters (PAEs) during childhood could increase the risk of excess weight. In addition, 10 studies found no correlation between these compounds and obesity. Conclusions: The effects of BPA and phthalates have diverse mechanisms; these chemicals disrupt some functional, structural, and epigenetic mechanisms that control energy homeostasis, appetite regulation, lipid metabolism, and adipogenesis. However, additional longitudinal studies are needed to confirm and validate the current findings.